Effects of Information Overload, Communication Overload, and Inequality on Digital Distrust: A Cyber-Violence Behavior Mechanism - Fan, Mingyue; Huang, Yuchen; Qalati, Sikandar Ali; Shah, Syed Mir Muhammad; Ostic, Dragana; Pu, Zhengjia (Frontiers in Psychology, 2021)
In recent years, there has been an escalation in cases of cyber violence, which has had a chilling effect on users’ behavior towards social media sites. This paper explores the causes behind cyber violence and provides empirical data for developing means for effective prevention. Using elements of the stimulus-organism-response (SOR) theory, we constructed a model of cyber violence behavior and tested it with data collected by means of an online questionnaire. Results from 531 valid questionnaires were used with structural equation modeling to empirically test the research hypotheses. Research shows that information inequality is a strong external stimulus with a significant positive impact on digital distrust and negative emotion. However, the effects of information overload on digital distrust and the adverse effects of communication overload on negative emotions should not be ignored. Both digital distrust and negative emotions have significant positive impacts on cyber violence, but the former has a stronger effect. This study also presents evidence for competitive mediation of digital distrust by information overload, information inequality, and cyber violence. The results of this study have implications for individual practitioners and scholars, for organizations, and at the governmental level regarding cyber violence behavior. To test our hypotheses, we have constructed an empirical, multi-dimensional model, including the role of specific mediators in creating relationships.